Noninvasive measurement of blood calcium concentration using electrocardiography in peripartum Jersey cows - Chiba, Yuto; Nozaki, Isamu; Itoh, Megumi; Kawamoto, Satoshi (Frontiers in Veterinary Science, 2023)
We previously developed a noninvasive method for measuring blood calcium concentration (Ca) in Holstein cows on site using electrocardiographic (ECG) variables and calving number, based on a high positive correlation between Ca. Jersey cows easily develop peripartum hypocalcemia compared with other dairy cows. The early detection and treatment of hypocalcemia are particularly important for Jersey cows because delayed treatment can result in various complications. In this study, to establish a simple, noninvasive, on-site diagnosis of hypocalcemia in perinatal Jersey cows, we attempted to create an equation for estimating Ca using ECG waveforms. Overall, 112 Jersey cows 0-2 days postpartum were used. The ECG findings of these cows were measured using the base-apex lead for 30 seconds and the corrected ST interval (STc = ST peak interval/SS peak interval 0.5 ) was calculated. Simultaneously, blood was collected from the tail vein, and the serum total Ca (tCa) and serum ionized Ca (iCa) were measured. Several items considered related to Ca were investigated. A strong positive correlation was observed between the tCa and iCa (r = 0.96). A positive correlation was observed between the tCa and STc −1 (r = 0.83). Furthermore, significant correlations were observed between skin temperature, calving number, vigor level, rumen movement, and auricle temperature (p < 0.05). Of these, multiple regression analysis was performed to calculate the tCa estimation formula with the STc and calving number (categorized into primipara, second parity, and third or more parity) as explanatory variables and the tCa as the objective variable (r = 0.85, p < 0.01). Of 15 postpartum Jersey cows, the estimation formula could mostly distinguish between cows with hypocalcemia, those with subclinical hypocalcemia, and normal cows. Blood Ca in peripartum Jersey cows can be noninvasively estimated using ECG variables and calving number.